DOI: 10.32469/10355/42618
|View full text |Cite
|
Sign up to set email alerts
|

Light scattering studies of organic field effect transistors

Abstract: LIST!OF!FIGURES! 2.1. The molecular structure of benzene. (a) and (b) show two ways of depicting the structure. (c) shows an alternate way that emphasizes the delocalization of electrons over the entire ring. .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 73 publications
(88 reference statements)
0
2
0
Order By: Relevance
“…Details of the OTS SAM deposition can be found in previous works from our research group. 40 The OTS solution was prepared in a freshly cleaned and dried glassware. Glassware was cleaned using Liquinox Critical Cleaning Detergent (Alconox Inc.) and dried in a closed oven (Model 20 GC Lab Oven) at 120 o C. The glassware was then allowed to cool to room temperature before use.…”
Section: Substrate Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the OTS SAM deposition can be found in previous works from our research group. 40 The OTS solution was prepared in a freshly cleaned and dried glassware. Glassware was cleaned using Liquinox Critical Cleaning Detergent (Alconox Inc.) and dried in a closed oven (Model 20 GC Lab Oven) at 120 o C. The glassware was then allowed to cool to room temperature before use.…”
Section: Substrate Preparationmentioning
confidence: 99%
“…It has been shown that the contact angle should be about 80 o . 40 A surface with a contact angle less than this is indicative of incomplete OTS coverage. If the above described protocol ever results in incompletely covered substrates during a particular session, it may be modified by dipping the substrates for a longer time (up to one minute).…”
Section: Substrate Preparationmentioning
confidence: 99%